Analisis Pengelolaan Sarana dan Prasarana Dalam Bidang Pendidikan - Icha Meidayanti; Septy Widyorini; Matilda moniz; M. Nurul Mu'minin; Febrianti Astutiningsih; Bahtiyar Heru Susanto (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Education is a planned and conscious effort to ensure that students receive lessons and actively develop and channel their potential to have good morals, namely religious, noble morals, honest and responsible personalities, as well as skills that will benefit them and society in the end (ABIDIN 2019:184). This research uses qualitative methods with data collection and analysis techniques carried out through literature studies from various books, scientific articles and other trusted sources. Literature study is a research method that involves reading books, articles, journals, websites, and other materials relevant to the research question, with the aim of understanding the assumptions and principles underlying the theory used as the basis for information for identification. Infrastructure refers to the basic infrastructure or facilities that support and enable the running of an activity. Infrastructure is usually fixed and related to a physical structure or larger system. or indirectly infrastructure to support education, for example school buildings, classrooms, laboratories, libraries. Educational facilities and infrastructure have a very important role in supporting the learning process. Facilities are direct tools or facilities used in learning activities, such as books, projectors and whiteboards. Infrastructure is the basic infrastructure that supports the running of activities, such as school buildings, classrooms and laboratories. Good management of facilities and infrastructure aims to create a comfortable, efficient and effective learning environment.